Translating the Medieval Icelandic Romance-Sagas ... - Hall, Alaric (unknown, 2014)
'Translating the Medieval Icelandic Romance-Sagas' is a short note surveying recent work done on translating romances composed in medieval Iceland into English, focusing on translations produced at the University of Leeds. It describes the ongoing project of the author and his collaborators to produce further translations for free-access publication. ...